Ecologically Sustainable Organizations: An Institutional Approach - Jennings, P. Deveraux; Zandbergen, Paul A. (Academy of Management Review, 1995)
Our main objective in this article is to join the growing group of green organization theorists by demonstrating the usefulness of institutional theory as an approach to ecologically sustainable organizations. Institutional theory helps to understand how consensus is built around the meaning of sustainability and how concepts or practices associated with sustainability are developed and diffused among organizations. We extend institutional theory by offering hypotheses in four different areas: (a) the incorporation of values into organizational sustainability, (b) the study of institutions as distinct elements within systems, (c) the study of institutions as distinct spheres, and (d) the construction of paradigms that support organizational sustainability. We then offer possible modifications to institutional theory that are suggested by the extension to a new area of study. Among them are the consideration of natural constraints on sense making and paradigm construction, the study of regional networks, and the recognition of the role of individual actors. Finally, we discuss possible avenues for future research by drawing on research that we are currently conducting.